Metric Analysis of Permanent and Deciduous Teeth from Bronze Age Tell Leilan, Syria - Scott Haddow; Nancy C. Lovell (Dental Anthropology Association, 2003)
Between 1979 and 1989 the skeletal remains of 21 adults and 38 children, yielding 317 permanent and 134 deciduous teeth, were recovered at Tell Leilan, Syria, the site of a major urban center during the emergence of complex state society in northern Mesopotamia in the mid-third millennium BC. Tooth crown dimensions (faciolingual and mesiodistal diameters, total crown area, and molar crown area) are presented and the last two serve as the primary units of comparison for a diachronic interpretation of tooth size variation in the ancient Near East. Both permanent and deciduous dental data support the pattern of dental reduction since the Middle Paleolithic that has been documented for Asia and Europe. The total crown areas for the permanent and deciduous dental samples, 1189 mm2 and 497 mm2 respectively, place this archaeological population at the smaller end of the crown area scale for the Near East; smaller in size than nearby Paleolithic and Neolithic populations. Given the paucity of odontological data for this area, this study contributes to the odontometric history of Mesopotamia and as a summary compilation and comparison of previously conducted odontometric work as it relates to the phenomenon of dental reduction within the ancient Near East.